Diamond: A Biography - Grossman, A., Truman, B.. (Chicago, New York Contemporary Books, Inc., 1987)
Examines the sacrifices and achievements of the legendary singer-songwriter and traces his struggles, failures, and successes, from his early years growing up in Brooklyn to his most recent album
Keywords: Biography